2011
DOI: 10.1063/1.3667291
|View full text |Cite|
|
Sign up to set email alerts
|

Photoacoustic determination of the speed of sound in single crystal cyclotrimethylene trinitramine at acoustic frequencies from 0.5 to 15 GHz

Abstract: We report photoacoustic measurements of the quasi-longitudinal speed of sound along different crystallographic directions in the energetic molecular crystal cyclotrimethylene trinitramine (RDX). Measurements in (100)-oriented RDX were made using two complimentary techniques to probe acoustic frequencies from 0.5 to 15 GHz to resolve large discrepancies in reported sound speed values measured using different techniques and frequency ranges. In impulsive stimulated light scattering (ISS), two laser beams were cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…2) and that the acoustic phonon specific heat is close to its Dulong-Petit value, as discussed above, then this would give an interlayer acoustic phonon velocity v c  3 c /(c acoustic )  3 x 10 5 cm/s, (6) which is actually a value fairly typical for organic molecular crystals. 30,31 Since v c is probably somewhat smaller than this, reflecting the weak interlayer coupling, the mean-free-path must instead be at least a few layers.…”
Section: Rubrene Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2) and that the acoustic phonon specific heat is close to its Dulong-Petit value, as discussed above, then this would give an interlayer acoustic phonon velocity v c  3 c /(c acoustic )  3 x 10 5 cm/s, (6) which is actually a value fairly typical for organic molecular crystals. 30,31 Since v c is probably somewhat smaller than this, reflecting the weak interlayer coupling, the mean-free-path must instead be at least a few layers.…”
Section: Rubrene Results and Discussionmentioning
confidence: 99%
“…30,31 Since v c is probably somewhat smaller than this, reflecting the weak interlayer coupling, the mean-free-path must instead be at least a few layers.…”
Section: Rubrene Results and Discussionmentioning
confidence: 99%
“…[34] Being crystalline and light, organic crystals are expected to deliver high power-to-weight ratios in energy-transducing and acoustic devices.T he longitudinal wave speeds (v)i n organic crystals,given by afamily of contours at v = (E/1) 1/2 in Figure 1b,a re 0.13-5.5 10 3 ms À1 ,w ith an average of 2.24 10 3 ms À1 .T hese values are in line with speeds obtained by ultrasonic pulse-echo,r esonant ultrasonic spectroscopy,i mpulsive stimulated thermal scattering, and Brillouin light scattering. [35,36] Organic crystals (see Figures 1a and 2a,a sw ell as Table S9) typically have Youngsm oduli (E)i nt he range 1-25 GPa, with approximately 8% having E < 1GPa and approximately 8% with E > 25 GPa (E ¯= 12.05 GPa, E ˜= 10.35 GPa, s = 8.35 GPa). Theh ardness (H)o fo rganic crystals is between 0.04 and 1.67 GPa (H ¯= 0.50 GPa, H ˜= 0.40 GPa, s = 0.35 GPa).…”
Section: Stiffness and Hardness Of Organic Crystalsmentioning
confidence: 99%
“…Haycraft et al compare results for K T from a number of experimental and computational studies. Although there is a sizable disagreement among a few studies over the value of a particular elastic constant (about a 40% deviation ), the reported results for K T all lie within the range 11.2–12.3 GPa, if one takes the true value of K T to be the average of that produced by the Voigt and Ruess schemes. Sewell and Bennett present Young’s modulus E and Poisson ratio ν predictions for RDX at 304 and 333 K. These quantities are obtained from Monte Carlo simulations of the elastic constants.…”
Section: Pure Componentsmentioning
confidence: 90%